Effect of nozzle distance and cutting parameters on MQL machining of AISI 1045 - Amiril Sahab, Abdul Sani; Erween, Abd Rahim; A. Z., Hishamudin (IOP Publishing, 2019)
Proper selection of nozzle distance during minimum quantity lubrication (MQL) machining can result in better performance of cutting force and tool life. This study emphasizes the effect of MQL nozzle distance from the cutting edge during the turning operation of AISI 1045 medium carbon steel. Machining operation at three levels of MQL nozzle distance with different cutting parameters are performed in order to evaluate the cutting force, tool wear and tool life of an uncoated cermet cutting insert. Results have shown significant reduction of the cutting force and tool wear progression which led to the improvement of the cutting tool life by keeping the distance of the MQL nozzle near to the cutting zone. Based from the experimental results, it is apparent that the appropriate MQL parameters including the nozzle distance showed a substantial contribution to the cutting performance and tool wear progression.